Controllable molecular doping in organic single crystals toward high-efficiency light-emitting devices - An, Ming-Hui; Ding, Ran; Ye, Gao-Da; Zhu, Qin-Cheng; Wang, Ya-Nan; Xu, Bin; Xu, Mei-Li; Wang, Xue-Peng; Wang, Wei; Feng, Jing; Sun, Hong-Bo (Organic electronics, 2021)
Organic single-crystalline semiconductors have drawn significant attention in the area of organic electronic and optoelectronic devices due to their superiorities of highly ordered structure, high carrier mobility and low impurity content. Molecular doping technique has made great progress in improving device performance via optimizing the optical and electrical properties of organic semiconductors. In particular, this technique has been attempted by taking fluorescent dye-molecules as the emissive dopants to tune emission color and improve device performance of organic single crystals. Up to now, there are few reports about the use of molecular doping in organic single crystals to optimize their intrinsic electrical properties. Here, we have introduced the controllable molecular doping as a feasible approach toward manipulating charge carrier transport properties of organic single crystals. Upon optimization of doping concentration, balanced carrier transport can be realized in 5,5′-bis(4-trifluoromethyl phenyl) [2,2’] bithiophene (P2TCF3)-doped 1,4-bis(4-methylstyryl) benzene (BSB–Me) crystals. Organic light-emitting devices (OLEDs) based on these doped crystals achieve a maximum luminance of 423 cd/m2 and current efficiency of 0.48 cd/A. It demonstrates that high-efficiency crystal-based OLEDs are of great significance for the development of organic electronics, especially for display and lighting applications. [Display omitted] •The n-type P2TCF3 has been introduced as dopant into a p-type BSB-Me host crystal.•Molecular doping is employed for realizing balanced carrier transport.•The comparable hole and electron mobilities can be obtained in doped crystals.•The luminance of doped crystal-based OLEDs is 3.5 times that of undoped crystal.•The current efficiency is correspondingly increased by 3.2 times.